Sulfide stress cracking of nickel-containing low-alloy steels - Iannuzzi, Mariano; Kappes, M.; Rebak, R.; Carranza, R. (2014)
Low-alloy steels (LAS) are extensively used in oil and gas (O&G) production due to their good mechani- cal properties and low cost. Even though nickel improves mechanical properties and hardenability with low penalty on weldability, which is critical for large subsea compo- nents, nickel content cannot exceed 1-wt% when used in sour service applications. The ISO 15156-2 standard limits the nickel content in LAS on the assumption that nickel concentrations above 1-wt% negatively impact sulfide stress cracking (SSC) resistance. This restriction excludes a significant number of high-strength and high-toughness alloys, such as Ni-Cr-Mo (e.g., UNS G43200 and G43400), Ni-Mo (e.g., UNS G46200), and Ni-Cr-Mo-V grades, from sour service applications and can be used only if suc- cessfully qualified. However, the standard is based on controversial research conducted more than 40 years ago. Since then, researchers have suggested that it is the micro- structure that determines SSC resistance, regardless of Ni content. This review summarizes the advantages and dis- advantages of nickel-containing LAS in terms of strength, weldability, hardenability, potential weight savings, and cost reduction. Likewise, the state of knowledge on the effect of nickel on hydrogen absorption as well as SSC ini- tiation and propagation kinetics is critically reviewed.